Answers

  • Brainly User
2016-03-07T00:41:45+08:00
Solve by substitution:
Equation 1:  9x - 5y = 8
Equation 2:  15x - 15y = 1
                    15x = 1 + 15y
                    15x/15 = 1/15 -+15y/15  
                    x = y + 1/15

Solution:
Step 1: Substitute y + 1/15 for x in Equation 1
9x - 5y = 8

9 (y+ 1/15) - 5y = 8

9y + 9/15 - 5y = 8

9y - 5y = 8 -9/15

4y = 8 - 3/5

20y = 40 - 3

20y = 37

20y/20 = 37/20

y = 37/20

Step 2:  Substitute 37/20 for y in:

x = y + 1/15

x = 37/20 + 1/15

x = 111/60  +  4/60

x = 115/60 or 23/12

Check:
9x - 5y = 8
9(23/12) - 5(37/20) = 8
69/4 - 37/4 = 8
32/4 = 8
8 = 8 (true)
------------------
15x -15y = 1
15(23/12) - 15(37/20) = 1
115/4 - 111/4 = 1
4/4 = 1
1 = 1  (true)





0